Growth performance and immune response of broiler chickens to oral administration of Parquetina nigrescens leaf extracts (Agriculture, Food, and Natural Resources Journal, 2025)
The study was to determine the effect of Parquetina nigrescens leaf extract on the performance, health status and immunological response of broiler chickens. Fresh leaves of Parquetina nigrescens were harvested and blended, using 10 g of leaves in 200 ml of water, this was administered in the first 5 days in the starter and finisher phases. Two-hundred-day old Arbor acres plus strains of broilers were assigned to five dietary treatments, four replicates with forty birds per treatment. The treatments were as follows: treatment 1: positive control – commercial antibiotics was used, treatment 2: negative control without commercial antibiotics while treatments 3, 4, 5 birds were administered 0.2, 0.4 and 0.6 ml of Parquetina nigrescens leaf extract per bird respectively. The design of the experiment was completely randomized design (CRD). Performance, hematological, serum biochemical and immunological responses as well as the relative organ weights were investigated using standard procedures. Data were subjected to one-way Analysis of Variance while significant differences were determined using Duncan’s multiple range tests. The results showed that there were significant differences (p
Keywords: Antibiotics; Biochemical; Growth; Haematological; Serum